Analisis Faktor Layanan, Reputasi dan Keamanan yang Mempengaruhi Keputusan Gen Z Menggunakan Perbankan Syariah - Lauza, Atiqa; Rasyidin, M.; Saleh, M.; Zulfikar, Zulfikar; Nova, Nova; Rizkina, Azka (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
TSharia banking is a bank that conducts business based on the principles of Islamic law or Sharia. Bank Shariah has introduced various products with features and amenities aimed at attracting Generation Z to use Bank Shariah's services. The objective of this study is to analyze the factors that influence decisions regarding the use of Islamic banking services. The subject of this research is Gen Z’s in Aceh. This type of research uses a quantitative approach. Data sources using online or electronic questionnaires with Google Forms Media. The data collection method uses an anonymous demographic technique with a sample size of 102 respondents. This study examines three factors of Shariah banking users' decisions to influence their decision to use Shariah banking services among Gen Z’s in Aceh, such as service, reputation and security variables. The results show that service, reputation and security variables influence Gen Z's decision of legitimate banking services in Aceh.